Immobilization of Actinide Radwaste into a Perovskite-Like Matrix by Self-Propagating High-Temperature Synthesis; Atomic Energy; Vol. 131, iss. 1 - Dolmatov O. Yu. Oleg Yurevich; Semenov A. O. Andrey Olegovich; Kuznetsov M. S. Mikhail Sergeyevich; Permikin A. A. Anton Andreevich; Balachkov M. M. Maxim Mikhailovich (2021, 2021)
Title screen